Technologies for the formation of teamwork skills in children of preschool educational organizations - Dilfuza Nuriddin-qizi Djurayeva (Universitas Muhammadiyah Sidoarjo, 2022)
This article discusses the issues of building a team and technology of teamwork in preschool educational institutions. Also, the results of the analysis of the concepts “team building”, “team skills”, “team spirit” are presented. In particular, the article provides ways to create ideal teamwork, as well as pedagogical, psychological and organizational conditions for teamwork methodology.